Engaging Higher Education Learners With Transmedia Play - Gunness, Aneeshta; Dickinson, Sonia; McNair, Hamish (2018)
This article documents the application of transmedia play in a higher education business context, providing a case study of how transmedia play can be infused into an undergraduate marketing course. We share our findings regarding learner experience and engagement, detailing results from structured interviews with 22 course participants. Evidence shows that the transmedia approach has value and can be successfully enacted in an undergraduate course to create connected learning opportunities and elicit cognitive, affective, and behavioral engagement. However, we note that the participatory nature of the pedagogy did create challenges for digital novices. In order to transition digital novices from peripheral to full participants in a transmedia learning community context, further research is warranted.